Mathematical modeling of the slow component of oxygen uptake kinetics in front crawl - Machado, L.; Querido, A.; Keskinen, K. L.; Fernandes, R.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
This work presents a mathematical method to model the VO2 kinetics during heavy exercise. This methods is able to discriminate between the different components of the oxygen uptake, including the basal, cardiodynamic, fast and slow components. Each of these components is fully characterized, not only in amplitude, but also in time of Start of that component. The method is applied to two swimmers, and the results are presented, resulting in both cases in a good description of the slow component for oxygen uptake.